(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
The RFID (Radio Frequency Identification technology) is actually one of most used options to the identification of products because it allows to improve the process related with the management of product information in the supply chain and medical environments. Its features make RFID the best option in dentification products process over other systems such as barcodes. However, according to the references consulted, there are few methodologies that guide the user on how to implement this technology in the environments indicated. The present article proposes a methodology for the implementation of RFID, for which we realize a research where existing methodologies are discussed to finally propose a methodology that addresses technological and managerial aspects.